Failure analysis of mechanical & electrical components - Moe, Hein Phyu (2017)
Machines or devices are susceptible to failure at some point of operation and some are designed to have a certain lifetime. Failure before their expected lifetime is highly undesirable because it can lead to delay of operation, loss of money, and serious hazards to lives in the working environment. Failure analysis allows to study the root cause of premature failures. In this study, failure analysis is carried out on two components, supporting springs and conductors, of a failed circuit breaker to find out if they are responsible for the cause of breaker failure. Knowing which, manufacturers can modify the design accordingly or operators can take preventive measures to reduce the occurrence rate of failure in the future. Metallographic techniques such as sample preparation, microscopy, SEM and EDX, and hardness testing are used for data collecting and fault tree analysis is used for guidance and conclusion. The springs were investigated first since a pair of springs was found to be in their pre-set lengths. Results from metallography suggest that deformation is resulted from the overheated circuit instead. When failure analysis was performed on conductors, cumulated layers of oxides, probably promoted by arcing, on contact surfaces were found to be a proximate cause of breaker failure. Due to high contact resistance of oxide layers, localized heating occurred on contact surfaces eventually leading to erosion, sticking and welding of contacts. Among available corrective actions, a usual clean-up of contact surfaces is suggested. While this study shows a proximate cause of failure led by accumulation of oxide layers, further studies on mating contacts, and components at entry point are recommended to gain a better and accurate understanding on the mode of circuit breaker failure.